Graduates’ English communicative competence and its impact on academic success: Implications for EFL learning in Bangladeshi public universities - Protiva Rani Karmaker; Rakib Al Hasan (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2025)
In Bangladesh’s EFL context, English communicative competence plays a critical role in shaping students’ academic success. This study examines the impact of English language skills on the educational experiences of public university graduates and identifies key instructional and curricular gaps. Using a mixed-methods explanatory sequential design, the study surveyed 100 graduates from three major public universities and conducted semi-structured interviews to explore their language challenges and perceptions. Quantitative data were analyzed using descriptive statistics, while qualitative responses underwent thematic analysis. Findings reveal that although many graduates self-rated their English skills as “good,” significant deficiencies, particularly in speaking and writing, frequently hindered academic tasks such as essay writing, presentations, and research communication. Notably, over 60% of participants reported a mismatch between university English instruction and the language demands of academic work. Qualitative insights further emphasize the emotional struggles and performance anxieties associated with low communicative competence. The study highlights the pressing need for curriculum reforms that focus on English for Academic Purposes (EAP), provide interactive speaking opportunities, and incorporate performance-based assessments. These findings advocate for skill-based, context-aware EFL instruction to better support academic achievement and professional preparedness in Bangladeshi higher education.